THE RELATIONSHIP BETWEEN THE USE OF TEACHING AIDS AND SCIENCE CONCEPT UNDERSTANDING IN ELEMENTARY SCHOOL STUDENTS - Handriadi Handriadi; Felipe Souza; Rafaela Lima; idam Mustofa (Yayasan Adra Karima Hubbi, 2025)
Developing a strong understanding of scientific concepts is critical for elementary school students as it forms the foundation for advanced learning and problem-solving skills. However, traditional teaching methods often fail to engage students effectively, leading to superficial understanding and low retention of science concepts. The use of teaching aids has been identified as a potential strategy to address this issue by making abstract concepts more tangible and interactive. This study aims to investigate the relationship between the use of teaching aids and the understanding of science concepts among elementary school students. A correlational research design was employed, involving 120 fifth-grade students from multiple schools. Data were collected using a science concept understanding test and an observation checklist to measure the extent and effectiveness of teaching aid usage. The results revealed a significant positive correlation between the use of teaching aids and students’ understanding of science concepts. Students exposed to teaching aids demonstrated higher levels of engagement, comprehension, and retention compared to those who received traditional instruction. These findings emphasize the importance of integrating teaching aids into science lessons to enhance learning outcomes. The study concludes by recommending the widespread use of teaching aids to support effective science education in elementary schools.